Sulfur-doped graphitized nanocarbon cages, methods of making the same, and carbon-based catalysts, methods of making the same, and applications
Patent Information
- Application Number
- CN202310163632.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2022-02-25
- Filing Date
- 2023-02-24
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2043-02-24
AI Technical Summary
尽管有关纳米碳材料的掺杂改性及性能的研究取得了诸多进展,但是对于其中的一些基本问题仍未形成共识,依然需要对掺杂改性的纳米碳材料及其制备方法和催化性能进行深入研究
[0021] The sulfur-doped graphitized carbon nanocages provided by this invention are used to make carbon-based catalysts containing platinum, which is beneficial to improve the oxygen reduction reaction (ORR) activity of fuel cell catalysts (Pt/C catalysts) and to reduce the overpotential in the hydrogen evolution reaction (HER) of electrocatalysts in water electrolysis, thereby improving the specific activity.
Smart Images

Figure CN116654902B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of carbon-based catalyst preparation, specifically to sulfur-doped graphitized carbon nanocages and their preparation methods, as well as carbon-based catalysts, their preparation methods, and applications. Background Technology
[0002] A fuel cell is a power generation device that converts the chemical energy of fuel into electrical energy directly through an electrochemical reaction without combustion. It has advantages such as high energy density, fast start-up, and high energy conversion efficiency, and is considered one of the most promising power generation technologies.
[0003] Currently, platinum-carbon catalysts (Pt / C) are the most widely used catalysts in fuel cells. Commercially, 40% Pt / C catalysts are prepared by reducing chloroplatinic acid impregnated inside and on the surface of Vulcan XC-72 carbon black into platinum nanoparticles via chemical reduction. However, during use, the significant decrease in platinum surface area due to platinum dissolution and agglomeration greatly affects the lifespan of the Pt / C catalyst. Therefore, developing catalysts with high catalytic activity and stability is of great value for reducing costs and promoting the practical application of fuel cell technology.
[0004] PEM (Potassium Ether Electrolysis) water electrolysis technology, with its high electrolysis efficiency, safety, reliability, compact structure, and rapid response to renewable energy, is widely recognized as one of the most promising hydrogen production technologies. Currently, the anode and cathode catalysts for PEM water electrolysis are entirely dependent on imports. With the rapid development of hydrogen energy, PEM water electrolysis technology has a huge market potential, and the demand for catalysts will increase rapidly. However, the anode and cathode catalysts used in PEM water electrolysis are both precious metal catalysts, resulting in high catalyst costs. Platinum-carbon catalysts are the cathode catalysts in PEM water electrolysis technology and are one of the core components of the technology. Manufacturing highly active, low-cost PEM water electrolysis cathode catalysts is a hot research topic.
[0005] Carbon nanocages are hollow carbon nanomaterials coated with graphite layers. Their surface structure resembles porous carbon, with pore sizes ranging from 2-100 nm and generally large specific surface areas. Due to their low density, high specific surface area, unique porous structure, strong corrosion resistance, and good electrical conductivity, they have recently shown exceptionally promising applications as catalyst supports, attracting widespread research. To improve the performance of carbon nanomaterials and adapt them to various applications, researchers often introduce heteroatoms (such as oxygen and nitrogen atoms) into them to enhance their performance. Although significant progress has been made in the research on the doping modification and properties of carbon nanomaterials, consensus has not yet been reached on some fundamental issues, and further in-depth research is needed on doped carbon nanomaterials, their preparation methods, and catalytic performance. Summary of the Invention
[0006] The purpose of this invention is to overcome the problems of low mass-to-specific-activity of Pt / C catalysts in the prior art, and to provide a sulfur-doped graphitized carbon nanocage and its preparation method, as well as a carbon-based catalyst and its preparation method and application. Using the sulfur-doped graphitized carbon nanocage provided by this invention as a support, combined with the noble metal platinum, the catalytic activity of the catalyst can be improved.
[0007] To achieve the above objectives, the first aspect of the present invention provides a sulfur-doped graphitized carbon nanocage, wherein the sulfur-doped graphitized carbon nanocage has a hollow cage-like structure with a diameter of 2-100 nm and a sulfur atom molar percentage content of 0.5-10% as measured by XPS.
[0008] Preferably, the sulfur-doped graphitized carbon nanocage has a carbon molar percentage of 60-98%, a sulfur molar percentage of 0.5-10%, and an oxygen molar percentage of 0.5-30%, as determined by X-ray photoelectron spectroscopy.
[0009] During their research, the inventors discovered that sulfur, similar to nitrogen in electronegativity, also possesses a lone pair of electrons. Doping sulfur into carbon nanocages alters the local charge distribution of the carbon material, and the resulting electrostatic forces or surface alkaline sites effectively adsorb metal ions, thereby enhancing the chemical activity of the carbon material. Sulfur exhibits strong interaction with platinum, and its anchoring effect on platinum contributes to the catalyst's stability, potentially further improving the performance of platinum-carbon catalysts. Through further research, the inventors used sulfur-doped graphitized carbon nanocages with specific diameters and a sulfur atom molar percentage of 0.5-10% as a support to prepare platinum-containing carbon-based catalysts. This process improves the oxygen reduction reaction (ORR) specific activity of fuel cell catalysts (Pt / C catalysts) and reduces the overpotential in the hydrogen evolution reaction (HER) of electrocatalysts in water electrolysis, further enhancing the specific activity.
[0010] A second aspect of the present invention provides a method for preparing sulfur-doped graphitized carbon nanocages, the method comprising the following steps:
[0011] (1) Provide a solution containing a transition metal salt, a carbon source and a solvent, and then dry it to obtain a precursor;
[0012] (2) Under an inert or reducing atmosphere, the precursor obtained in step (1) is subjected to high-temperature pyrolysis at a temperature of 850-1300℃ to obtain pyrolysis products.
[0013] (3) The pyrolysis product is acid washed, then solid-liquid separation and drying are performed to obtain nano-carbon cages;
[0014] The method further includes steps (4-1) and / or (4-2), wherein,
[0015] (4-1) The nano-carbon cage is mixed with a sulfur source and then subjected to high-temperature treatment at 300-1500℃;
[0016] (4-2) The nano-carbon cage is impregnated with an impregnation solution containing a sulfur source and then dried.
[0017] A third aspect of the present invention provides a carbon-based catalyst containing platinum, the catalyst comprising a support and platinum supported on the support, wherein the support contains either the sulfur-doped graphitized carbon nanocages described in the first aspect or the sulfur-doped graphitized carbon nanocages prepared by the method described in the second aspect.
[0018] A fourth aspect of this invention provides a method for preparing a carbon-based catalyst containing platinum, the method comprising:
[0019] After mixing the support with a platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction or gas-phase reduction; the support contains the sulfur-doped graphitized carbon nanocages described in the first aspect or the sulfur-doped graphitized carbon nanocages prepared by the method described in the second aspect.
[0020] The fifth aspect of the present invention provides the application of the carbon-based catalyst containing platinum as described in the third aspect or the carbon-based catalyst containing platinum prepared by the method described in the fourth aspect in water electrolysis or fuel cells.
[0021] The sulfur-doped graphitized carbon nanocages provided by this invention are used to make carbon-based catalysts containing platinum, which is beneficial to improve the oxygen reduction reaction (ORR) activity of fuel cell catalysts (Pt / C catalysts) and to reduce the overpotential in the hydrogen evolution reaction (HER) of electrocatalysts in water electrolysis, thereby improving the specific activity. Attached Figure Description
[0022] Figure 1 This is a TEM image of the sulfur-doped carbon nanocage prepared in Example A-1;
[0023] Figure 2 This is the XPS S2p image of the sulfur-doped carbon nanocage prepared in Example A-1;
[0024] Figure 3 This is the BJH pore size distribution curve of the sulfur-doped carbon nanocage prepared in Example A-1;
[0025] Figure 4 This is a TEM image of the platinum-supported catalyst prepared in Example A-1;
[0026] Figure 5These are TEM images of the platinum-supported catalysts prepared in Examples A-7;
[0027] Figure 6 This is a TEM image of the sulfur-nitrogen-doped carbon nanocages prepared in Example B-1;
[0028] Figure 7 This is the XPS S2p image of the sulfur-doped carbon nanocage prepared in Example B-1;
[0029] Figure 8 This is the XPS N1S image of the sulfur-doped carbon nanocage prepared in Example B-1;
[0030] Figure 9 This is a TEM image of the platinum-supported catalyst prepared in Example B-1;
[0031] Figure 10 This is a TEM image of the platinum-supported catalyst prepared in Example B-6. Detailed Implementation
[0032] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0033] In this invention, the hollow cage shape has the conventional interpretation in the art, specifically referring to a hollow sphere or quasi-sphere formed by a graphitized carbon layer surrounding it.
[0034] In this invention, the term "mesopore" is defined as a pore with a diameter in the range of 2-50 nm.
[0035] In this invention, the term "sulfur-doped graphitized carbon nanocage" specifically refers to sulfur elements existing in various forms within the graphitized carbon nanocage during its preparation process.
[0036] In this invention, the terms "pyrrole nitrogen," "pyridine nitrogen," "graphite nitrogen," and "oxidized nitrogen" have their conventional meanings in the art, specifically referring to: pyridine nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 398.7-399.1 eV in X-ray photoelectron spectroscopy; pyrrole nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 398.8-400.2 eV in X-ray photoelectron spectroscopy; graphite nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 401.2-401.8 eV in X-ray photoelectron spectroscopy; and oxidized nitrogen as a nitrogen species identified by characteristic spectral peaks corresponding to binding energies of 402.8-403.6 eV in X-ray photoelectron spectroscopy.
[0037] According to one specific embodiment of the present invention, the sulfur atomic molar percentage content measured by XPS is 0.5-10%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10%.
[0038] According to one specific embodiment of the present invention, the sulfur-doped graphitized carbon nanocage has a hollow cage-like structure with a diameter of 2-100 nm, preferably with a diameter of 2-50 nm, and more preferably with a diameter of 5-30 nm.
[0039] Preferably, the molar percentage of carbon in the sulfur-doped graphitized carbon nanocage, as determined by X-ray photoelectron spectroscopy, is 60-98%, the molar percentage of sulfur is 0.5-10%, and the molar percentage of oxygen is 0.5-30%. Specifically, the molar percentage of carbon can be, for example, 60, 65, 70, 75, 80, 85, 90, 95, or 98%; the molar percentage of sulfur can be, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10%; and the molar percentage of oxygen can be, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, or 30%.
[0040] According to a preferred embodiment of the present invention, the sulfur-doped graphitized carbon nanocage is composed of carbon, oxygen, and sulfur, and X-ray photoelectron spectroscopy shows that the molar percentage of carbon on the surface of the sulfur-doped graphitized carbon nanocage is 60-98%, the molar percentage of sulfur is 0.5-10%, and the molar percentage of oxygen is 0.5-30%; preferably, the molar percentage of carbon is 85-97%, the molar percentage of sulfur is 0.5-10%, and the molar percentage of oxygen is 2-14%.
[0041] The oxygen element in the sulfur-doped graphitized carbon nanocage can be oxygen element that exists in various forms formed in the graphitized carbon nanocage.
[0042] According to the present invention, preferably, in the Raman curve of the sulfur-doped graphitized carbon nanocage, I D / I G The value is less than 1.2, preferably less than 1.1, for example, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1. The sulfur-doped graphitized carbon nanocages provided by the present invention have obvious D peaks and G peaks, and have a certain degree of graphitization.
[0043] Preferably, the sulfur-doped graphitized carbon nanocage has two or more mesopore distribution peaks; more preferably, the first most probable pore size of the sulfur-doped graphitized carbon nanocage is 2-5 nanometers, for example 2, 3, 4 or 5 nanometers, and the corresponding second most probable pore size is 10-30 nanometers, for example 10, 15, 20, 25 or 30 nanometers.
[0044] Preferably, the thickness of the sulfur-doped graphitized carbon nanocage is 1-10 layers of graphitized carbon atoms, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10. The thickness of the sulfur-doped graphitized carbon nanocage is observed by high-resolution transmission electron microscopy (HRTEM).
[0045] According to a preferred embodiment of the present invention, the sulfur-doped graphitized carbon nanocage also contains nitrogen, and the molar percentage of nitrogen atoms measured by XPS is 0.5-10%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10%. In a more preferred case, the molar percentage of nitrogen atoms measured by XPS is 0.5-2%.
[0046] When the sulfur-doped graphitized carbon nanocage also contains nitrogen, the graphitized carbon nanocage can also be called a sulfur-nitrogen-doped graphitized carbon nanocage.
[0047] Preferably, based on the total molar amount of nitrogen, the molar percentage of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the sulfur-doped graphitized carbon nanocage, as measured by X-ray photoelectron spectroscopy, is greater than 80%, for example, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, or 100%.
[0048] Preferably, based on the total molar amount of nitrogen, the molar percentage of pyrrole nitrogen in the nitrogen on the surface of the graphitized carbon nanocage, as measured by X-ray photoelectron spectroscopy, is 70-100%, for example, 70, 75, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92, 93, 94, 95, 96, 97, 98, 99, or 100%, and the molar percentage of pyridine nitrogen is 0-30%, for example, 0, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 15, 20, 25, or 30%.
[0049] According to a preferred embodiment of the present invention, the molar percentage of carbon on the surface of the graphitized carbon nanocage, as measured by X-ray photoelectron spectroscopy, is 60-98%, for example 60, 65, 70, 75, 80, 85, 90, 95% or 98%; the molar percentage of nitrogen is 0.5-10%, for example 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10%; the molar percentage of oxygen is 1-25%, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 12, 14, 16, 18, 20 or 25%; and the molar percentage of sulfur is 0.5-5%, for example 0.5, 1, 2, 3, 4 or 5%.
[0050] More preferably, the sulfur-doped graphitized carbon nanocage has a carbon molar percentage of 85-97%, a nitrogen molar percentage of 0.5-3%, an oxygen molar percentage of 2-13%, and a sulfur molar percentage of 0.5-4.5%, as determined by X-ray photoelectron spectroscopy.
[0051] According to a preferred embodiment of the present invention, the sulfur-doped graphitized carbon nanocage is composed of carbon, oxygen, nitrogen and sulfur elements, and X-ray photoelectron spectroscopy shows that the molar percentage of carbon in the sulfur-doped graphitized carbon nanocage is 85-97%, the molar percentage of nitrogen is 0.5-3%, the molar percentage of oxygen is 2-13%, and the molar percentage of sulfur is 0.5-4.5%.
[0052] In this invention, the surface morphology of the material is characterized using high-resolution transmission electron microscopy (HRTEM). The HRTEM used is a JEM-2100 (Nippon Electron Ltd.), and the testing conditions are: accelerating voltage of 200 kV. The particle size of the nanoparticles and the number of carbon layers in the sample can be obtained by measuring the electron microscope images.
[0053] BET test method: In this invention, the pore structure properties of the sample are determined by a Quantachrome AS-6B analyzer, and the mesopore distribution curve is calculated from the desorption curve using the Barrett-Joyner-Halenda (BJH) method.
[0054] X-ray photoelectron spectroscopy analysis was performed on a Thermo Scientific ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software. The excitation source was monochromatic Al Kα X-rays with an energy of 1486.6 eV and a power of 150 W. The narrow scan penetration energy was 30 eV, and the baseline vacuum during analysis was 6.53 × 10⁻⁶. -9 mbar, electron binding energy was corrected using the C1s peak (284.6 eV) of elemental carbon, data processing was performed on Thermo Avantage software, and quantitative analysis was performed using the sensitivity factor method in the analysis module.
[0055] In this invention, the degree of graphitization of graphitized carbon nanocages is characterized by Raman spectroscopy at 1355 cm⁻¹. -1 The peak (D peak) is attributed to structural defects, consisting of amorphous carbon, at 1585 cm⁻¹. -1 The peak (G peak) is attributed to carbon in a planar structure. I0 is typically used. D / I G The degree of graphitization of a material is characterized by the intensity ratio of the D peak to the G peak. D / I G The higher the value, the more defects and the lower the degree of graphitization. The Raman spectrum of the material was obtained using an RM2000 microconfocal Raman spectrometer (Reinshaw product). Technical specifications: The excitation source was a He-Ne laser with a wavelength of 525 nm.
[0056] In the method for preparing sulfur-doped graphitized carbon nanocages provided by the second aspect of the present invention, sulfur is introduced in the final step to obtain sulfur-doped graphitized carbon nanocages with a specific structure. Sulfur can be introduced through steps (4-1) and / or (4-2), meaning it can be introduced in either step (4-1) or step (4-2), or partially in step (4-1) with the remainder introduced in step (4-2).
[0057] According to a preferred embodiment of the present invention, in step (1), there is no particular limitation on the method of forming the solution. For example, the solution can be formed by heating, and more preferably by heating and stirring. The present invention also does not particularly limit the heating temperature and the stirring rate, as long as the solution can be formed.
[0058] According to a preferred embodiment of the present invention, in step (1), the precursor is obtained by dissolving a transition metal salt and a carbon source in a solvent to form a homogeneous solution, and then removing the solvent from the homogeneous solution (drying).
[0059] According to the method provided by the present invention, preferably, in step (1), the carbon source is a nitrogen-free carbon source and / or a nitrogen-containing carbon source. Preferably, the nitrogen-free carbon source is at least one of citric acid, maleic acid, pyromellitic acid, terephthalic acid, and malic acid, more preferably citric acid; preferably, the nitrogen-containing carbon source is a nitrogen-containing organic carboxylic acid, more preferably ethylenediaminetetraacetic acid. When the carbon source is a nitrogen-containing carbon source, it is understood that nitrogen will be introduced into the sulfur-doped graphitized carbon nanocage, and the resulting carbon nanocage will contain a specific molar percentage of pyrrole nitrogen and / or pyridine nitrogen, giving the carbon nanocage particularly superior performance.
[0060] In a preferred embodiment, when the carbon source is a nitrogen-free carbon source, the amounts of the carbon source, transition metal salt, and sulfur source are such that, as measured by X-ray photoelectron spectroscopy, the graphitized carbon nanocages obtained have a carbon molar percentage of 60-98%, a sulfur molar percentage of 0.5-10%, and an oxygen molar percentage of 0.5-30%. More preferably, the graphitized carbon nanocages have a carbon molar percentage of 85-97%, a sulfur molar percentage of 0.5-10%, and an oxygen molar percentage of 2-14%, as measured by X-ray photoelectron spectroscopy.
[0061] In a preferred embodiment, when the carbon source is a nitrogen-containing carbon source, the amounts of the carbon source, transition metal salt, and sulfur source are such that, as measured by X-ray photoelectron spectroscopy, the graphitized carbon nanocages obtained have a carbon molar percentage of 60-98%, a nitrogen molar percentage of 0.5-10%, an oxygen molar percentage of 1-25%, and a sulfur molar percentage of 0.5-5%. More preferably, as measured by X-ray photoelectron spectroscopy, the sulfur-doped graphitized carbon nanocages have a carbon molar percentage of 85-97%, a nitrogen molar percentage of 0.5-3%, an oxygen molar percentage of 2-13%, and a sulfur molar percentage of 0.5-4.5%.
[0062] In a more preferred embodiment, when the carbon source is a nitrogen-containing carbon source, the amounts of the carbon source, transition metal salt, and sulfur source are such that the molar percentage of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the graphitized carbon nanocage, as measured by X-ray photoelectron spectroscopy, is greater than 80%.
[0063] In this invention, preferably, the transition metal salt is selected from one or more of the organic acid salts, carbonates, and basic carbonates of transition metals; preferably, the organic acid salt of the transition metal is an organic carboxylate salt of the transition metal that does not contain heteroatoms, preferably an acetate.
[0064] Preferably, the transition metal is at least one selected from iron, cobalt, nickel, and copper, and more preferably nickel.
[0065] According to a specific embodiment of the present invention, preferably, the transition metal salt is selected from basic nickel carbonate and / or nickel acetate.
[0066] According to a preferred embodiment of the present invention, the molar ratio of the transition metal salt to the carbon source, calculated as transition metal element, is 1:0.1-10, preferably 1:0.5-5, and more preferably 1:0.6-0.9. This preferred embodiment is more advantageous in improving the activity of the prepared nano-carbon cages when used as carbon-based catalysts.
[0067] The present invention does not particularly limit the type of solvent, as long as it can form a homogeneous solution. Preferably, the solvent is water and / or ethanol, more preferably water. The present invention also does not particularly limit the amount of solvent used, as long as it can form a homogeneous solution.
[0068] According to the present invention, preferably, in step (2), the high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 1-20℃ / min, preferably 5-10℃ / min, and then maintaining a constant temperature. A wide range of constant temperature time is available, taking into account both effectiveness and energy saving; preferably, the constant temperature time is 20-600 min, more preferably 60-480 min.
[0069] Preferably, the temperature of the high-temperature pyrolysis is 900-1200℃.
[0070] According to a preferred embodiment of the present invention, in step (2), the temperature is raised to the high-temperature pyrolysis temperature in two stages, specifically: first, the temperature is raised to 400-800℃, preferably 500-700℃, at a rate of 1-20℃ / min, preferably 5-10℃ / min, and held at that temperature for 20-600min, preferably 60-480min; then, the temperature is raised to the high-temperature pyrolysis temperature at a rate of 1-20℃ / min, preferably 5-10℃ / min, and held at that temperature for 20-600min, preferably 60-480min.
[0071] According to some embodiments of the present invention, preferably, in step (2), the inert atmosphere is provided by at least one of nitrogen, argon, neon, and helium; and / or,
[0072] The reducing atmosphere is provided by hydrogen and optionally an inert gas, which is at least one of nitrogen, argon, neon, and helium. There is no particular limitation on the hydrogen content in the reducing atmosphere, which can be 1-100% by volume.
[0073] According to some embodiments of the present invention, in step (3), the pyrolysis product is acid-washed using an acid pickling agent. Specifically, the pyrolysis product is mixed with the acid pickling agent. The present invention does not have a particular limitation on the mixing method; it can be mixed by ultrasound or stirring. The acid pickling agent can be an acid conventionally used in the art, as long as it can remove the transition metals in the pyrolysis product. Preferably, the acid pickling agent is an aqueous solution of inorganic acid and / or an aqueous solution of organic acid, preferably at least one of aqueous solutions of hydrochloric acid, sulfuric acid, nitric acid, and citric acid, more preferably an aqueous solution of hydrochloric acid. Preferably, the concentration of the aqueous solution of inorganic acid and / or the aqueous solution of organic acid is 0.1-10 mol / L; the pH value of the acid pickling agent is less than 7. The present invention does not have a particular requirement for the amount of the acid pickling agent used, as long as it can remove the transition metals in the pyrolysis product.
[0074] According to some embodiments of the present invention, preferably, in step (3), the pickling temperature is 20-120°C, more preferably 60-100°C; and the time is 0.1-48h, more preferably 4-12h.
[0075] The present invention does not have any particular limitation on the solid-liquid separation method described in step (3). It can be carried out by solid-liquid separation methods known in the art, such as filtration.
[0076] Step (3) of the present invention preferably includes washing the solid product obtained from solid-liquid separation before the drying. The washing is used to remove acid and metal ions remaining on the nano-carbon cages during the acid washing process. Therefore, various water washing methods that can wash the nano-carbon cages to neutrality are applicable to the present invention.
[0077] According to some embodiments of the present invention, the drying is used to remove water from the carbon nanocages. The drying can be performed under normal pressure or reduced pressure. Drying conditions may include a temperature of 80-140°C and a time of 6-10 hours.
[0078] In step (4-1), preferably, the high-temperature treatment temperature is 400-1200℃, for example, 400℃, 500℃, 600℃, 700℃, 800℃, 900℃, 1000℃, 1100℃ or 1200℃, more preferably, the high-temperature treatment temperature is 450-1100℃.
[0079] Preferably, the high-temperature treatment time is 30-300 min, for example, 30 min, 60 min, 90 min, 120 min, 150 min, 180 min, 210 min, 240 min, 270 min or 300 min.
[0080] The present invention offers a wide range of selectable heating rates for the high-temperature treatment, allowing those skilled in the art to make adaptive selections based on specific circumstances. This embodiment uses 5°C / min as an example for illustrative purposes, but the invention is not limited thereto.
[0081] The sulfur source is preferably selected from at least one of sulfur, hydrogen sulfide, carbon disulfide, sodium thiosulfate, thiophene, elemental sulfur, sulfate and sulfonate, and is more preferably sulfur.
[0082] Preferably, the amount of the carbon nanocage and the sulfur source is such that the sulfur-doped graphitized carbon nanocage obtained has a sulfur atom molar percentage content of 0.5-10% as measured by XPS, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10%, preferably 0.5-5%.
[0083] In step (4-2), preferably, the sulfur source is selected from at least one of sulfur, sodium thiosulfate, thiophene, elemental sulfur, sulfate and sulfonate, and more preferably sulfur.
[0084] Preferably, the solvent in the impregnation solution is selected from one or more of CCl4, CS2, cyclohexane, and n-hexane.
[0085] Preferably, the concentration of the sulfur source in the impregnation solution is 0.0004-0.02 g / mL.
[0086] The present invention does not particularly limit the impregnation method, and can be any impregnation method conventional in the art, such as equal volume impregnation or supersaturated impregnation, which will not be described in detail here.
[0087] Preferably, the amount of the carbon nanocage and the sulfur source is such that the sulfur-doped graphitized carbon nanocage obtained has a sulfur atom molar percentage content of 0.5-10% as measured by XPS, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10%, preferably 0.5-5%.
[0088] Preferably, the amount of the impregnation solution used is 5-15 mL relative to 1 g of the nano-carbon cage.
[0089] Preferably, the drying conditions include a temperature of 20-100℃ and a time of 5-10 hours.
[0090] A third aspect of the present invention provides a carbon-based catalyst containing platinum, the catalyst comprising a support and platinum supported on the support, wherein the support contains either a sulfur-doped graphitized carbon nanocage as described in the present invention or a sulfur-doped graphitized carbon nanocage prepared by the method described in the present invention.
[0091] Preferably, based on the total amount of the carbon-based catalyst, the platinum mass percentage is 0.5-70%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70%, and any value within any range of any two of these values. More preferably, based on the total amount of the carbon-based catalyst, the platinum mass percentage is 30-50%.
[0092] A fourth aspect of this invention provides a method for preparing a carbon-based catalyst containing platinum, the method comprising:
[0093] After mixing the support with a platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction or gas-phase reduction; the support contains sulfur-doped graphitized carbon nanocages as described in the first aspect or sulfur-doped graphitized carbon nanocages prepared by the method described in the second aspect.
[0094] Preferably, the amount of support and platinum source is such that, based on the total amount of the carbon-based catalyst, the mass percentage of platinum in the prepared catalyst is 0.5-70%, for example, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70%, and any value within any range of any two of these values. More preferably, based on the total amount of the carbon-based catalyst, the mass percentage of platinum is 30-50%.
[0095] According to a preferred embodiment of the present invention, after mixing the support and platinum source in the presence of a solvent, the mixture is reduced to a carbon-based catalyst containing metallic platinum via liquid phase reduction, comprising:
[0096] The support and platinum source are mixed in the presence of a solvent, and the pH is adjusted preferably to 8-12 (e.g., 8, 9, 10, 11 or 12). A reducing agent is added for reduction, and then the mixture is dried (preferably washed before drying) to obtain a carbon-based catalyst containing metallic platinum.
[0097] In this preferred embodiment, preferably, the platinum source is at least one of chloroplatinic acid, potassium chloroplatinate, sodium chloroplatinate, and other inorganic platinum salts.
[0098] Preferably, the platinum source is provided in the form of a solution, and its concentration is preferably 0.5 mol / L to 5 mol / L, for example 0.5, 1, 2, 3, 4 or 5 mol / L, and any value within any two of these values.
[0099] The present invention allows for a wide range of solvent selection; preferably, the solvent is water.
[0100] The pH is preferably adjusted using an alkaline solution, which may be a solution of one or more alkaline substances selected from sodium carbonate, potassium carbonate, ammonia, potassium hydroxide, and sodium hydroxide (preferably an aqueous solution).
[0101] In this preferred embodiment, the reducing agent is preferably selected from one or more of citric acid, ascorbic acid, formaldehyde, formic acid, ethylene glycol, sodium citrate, hydrazine hydrate, sodium borohydride, and glycerol.
[0102] In this preferred embodiment, the molar ratio of the reducing agent to the platinum source (calculated as Pt) is preferably between 2 and 100, for example, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, and any value within the range formed by any two of these values.
[0103] In this preferred embodiment, the reduction temperature is preferably 50-150℃, for example 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 110, 120, 130, 140, 150℃, and any value within any range formed by any two of these values. The reduction time is preferably 2-15h, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15h, and any value within any range formed by any two of these values.
[0104] In another preferred embodiment, the process of mixing the support and the platinum source in the presence of a solvent and then reducing them in the gas phase to obtain a carbon-based catalyst containing metallic platinum includes: mixing the support and the platinum source in the presence of a solvent, removing the solvent to obtain a precursor material, and then heat-treating the precursor material in a reducing atmosphere.
[0105] In this preferred embodiment, the heat treatment is preferably performed at 80-300°C (for example, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170, 180, 190, 200, 220, 240, 260, 280, 300°C, and any value within the range formed by any two of these values) for 1-4 hours.
[0106] In this preferred embodiment, the platinum source is selected from at least one of chloroplatinic acid, chloroplatinate, tetraammineplatinum acetate, and platinum acetylacetonate.
[0107] The present invention has a wide range of solvents that can be selected. Preferably, the solvent is one or more of water, alcohol solvents and ketone solvents, and more preferably, the solvent is water and / or ethanol.
[0108] In this preferred embodiment, the mixture is further further comprising: allowing the mixed material to stand before removing the solvent, preferably for 10 hours or more, more preferably 15-48 hours. This method is more conducive to the loading of platinum and the full dispersion of Pt on the carrier surface.
[0109] In this preferred embodiment, the drying temperature during solvent removal is below 100°C.
[0110] In this preferred embodiment, the reducing atmosphere can be provided by hydrogen and optionally an inert gas (the selection range can be the same as the selection range described above), more preferably by a mixed atmosphere of hydrogen and nitrogen; preferably, the hydrogen content in the mixed atmosphere is 5-50% by volume.
[0111] The fifth aspect of the present invention provides the application of the carbon-based catalyst containing platinum as described in the third aspect or the carbon-based catalyst containing platinum prepared by the method described in the fourth aspect in water electrolysis or fuel cells.
[0112] The platinum-containing carbon-based catalyst provided by this invention is beneficial for improving the oxygen reduction reaction (ORR) activity of fuel cell catalysts (Pt / C catalysts) and for reducing the overpotential in the hydrogen evolution reaction (HER) of electrocatalysts in water electrolysis, thereby increasing the specific activity. Since this invention primarily relates to catalyst improvement, there are no particular limitations on other operating conditions and structures when applying the platinum-containing carbon-based catalyst of this invention to water electrolysis or fuel cells. Those skilled in the art can make appropriate selections based on specific operating conditions.
[0113] According to the application of the present invention, the fuel cell is preferably a proton exchange membrane hydrogen fuel cell.
[0114] According to the application of the present invention, the platinum-containing carbon-based catalyst is preferably a platinum-carbon catalyst for the anode or cathode of a proton exchange membrane hydrogen fuel cell.
[0115] The present invention will be described in detail below through embodiments.
[0116] Unless otherwise specified, all reagents used in this invention are of analytical grade and are commercially available.
[0117] The specific instruments and parameters for characterization using high-resolution transmission electron microscopy (HRTEM), BET testing, X-ray photoelectron spectroscopy (XPS), and Raman spectroscopy are as described above and will not be repeated here.
[0118] ORR electrochemical performance testing was conducted using Solartron Analytical EnergyLab and Princeton Applied Research (Model 636A) instruments. The methods and testing conditions were as follows: The catalyst polarization curve (LSV) was measured at 1600 rpm in O2-saturated 0.1 M HClO4, and the electrochemical active area (ECSA) was measured in Ar-saturated 0.1 M HClO4. Stability testing was performed in O2-saturated 0.1 M HClO4, scanning for 5000 cycles within the range of 0.6 V–0.95 V (vs. RHE), followed by testing LSV and ECSA using the same method. For all tests, the catalyst was prepared as a uniformly dispersed slurry and coated onto a 5 mm diameter glassy carbon electrode. The platinum content of the catalyst on the electrode was controlled within the range of 1–4 μg. No iR correction was performed in the calculations.
[0119] Electrochemical performance testing of the HER was performed using Solartron Analytical EnergyLab and Princeton Applied Research (Model 636A). The methods and testing conditions were as follows: the catalyst polarization curve (LSV) was measured at 2500 rpm in N2-saturated 0.5 M H2SO4, and the electrochemical active area (ECSA) was measured in N2-saturated 0.5 M H2SO4. For all tests, the catalyst was prepared as a uniformly dispersed slurry and coated onto a 5 mm diameter glassy carbon electrode. The platinum content of the catalyst on the electrode was controlled within the range of 1-4 μg. No iR correction was performed in the calculations.
[0120] Preparation Example 1
[0121] This preparation example illustrates the preparation of carbon nanocages.
[0122] (1) Weigh 15g of basic nickel carbonate and 15g of citric acid, add them to a beaker containing 40mL of deionized water, stir and mix them evenly at 80℃, and continue to heat and evaporate to dryness to obtain a solid precursor.
[0123] (2) Place the precursor obtained in step (1) into a ceramic boat, then place the ceramic boat in the constant temperature zone of a tube furnace, introduce nitrogen gas with a flow rate of 80 mL / min, and heat it to 600℃ at a rate of 10℃ / min. After holding the temperature for 1 hour, continue to heat it to 900℃ at a rate of 10℃ / min and hold the temperature for 2 hours. Stop heating and cool it to room temperature under a nitrogen atmosphere to obtain the pyrolysis product.
[0124] (3) Add the pyrolysis product obtained in step (2) to an aqueous solution containing 2M hydrochloric acid and stir at 90°C for 8 hours. Then filter, collect the filtrate, wash with deionized water until the filtrate is neutral, and then dry the filter cake in a constant temperature oven at 120°C for 6 hours to obtain nano carbon cages.
[0125] TEM characterization of the carbon nanocages shows that the prepared material is a hollow cage-like carbon nanomaterial with a size of 5-30 nm.
[0126] The following examples illustrate sulfur-doped carbon nanocages and platinum-supported catalysts and their preparation.
[0127] Example A-1
[0128] Preparation of sulfur-doped carbon nanocages
[0129] Take 0.12 g of the nano-carbon cage prepared in Preparation Example 1, add 0.02 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 1100 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-doped nano-carbon cages. Figure 1 The sulfur-doped carbon nanocage TEM obtained. Figure 2 The image shows the XPS S2p plot of the prepared sulfur-doped carbon nanocages. Figure 3 The image shows the pore size distribution curve of the sulfur-doped carbon nanocage BJH. The material exhibits two mesopore distribution peaks at 3.82 nm and 24.77 nm, as measured by Raman spectroscopy. D / I G It is 1.09.
[0130] Preparation of platinum-supported catalysts
[0131] 0.06 g of sulfur-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added with stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The resulting mixture was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst. Figure 4 This is a TEM image of the prepared platinum-supported catalyst.
[0132] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0133] Example A-2
[0134] Preparation of sulfur-doped carbon nanocages
[0135] Take 0.12 g of the nano-carbon cage prepared in Preparation Example 1, add 0.02 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-doped nano-carbon cages.
[0136] Preparation of platinum-supported catalysts
[0137] 0.06 g of sulfur-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0138] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0139] Example A-3
[0140] Preparation of sulfur-doped carbon nanocages
[0141] Take 0.1 g of the nano-carbon cage prepared in Preparation Example 1, add 0.05 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-doped nano-carbon cages.
[0142] Preparation of platinum-supported catalysts
[0143] 0.06 g of sulfur-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0144] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0145] Example A-4
[0146] Preparation of sulfur-doped carbon nanocages
[0147] Take 0.10 g of the nano-carbon cage prepared in Preparation Example 1, add 0.05 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 450 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-doped nano-carbon cages.
[0148] Preparation of platinum-supported catalysts
[0149] 0.06 g of sulfur-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0150] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0151] Example A-5
[0152] Preparation of sulfur-doped carbon nanocages
[0153] Take 0.10 g of the nano-carbon cage prepared in Preparation Example 1, add 0.05 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 650 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-doped nano-carbon cages.
[0154] Preparation of platinum-supported catalysts
[0155] 0.06 g of sulfur-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0156] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0157] Example A-6
[0158] Preparation of sulfur-doped carbon nanocages
[0159] Take 0.10 g of the nano-carbon cage prepared in Preparation Example 1, add 0.05 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 1100 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-doped nano-carbon cages.
[0160] Preparation of platinum-supported catalysts
[0161] 0.06 g of sulfur-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0162] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0163] Comparative Example 1
[0164] 0.06 g of the nano-carbon cage prepared in Preparation Example 1 was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added with stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst. The platinum content in the catalyst is listed in Table 1.
[0165] Example A-7
[0166] Preparation of platinum-supported catalysts
[0167] Take 0.1 g of the sulfur-doped carbon nanocage material prepared in Example A-1, add 2.73 mL of chloroplatinic acid aqueous solution (1 g chloroplatinic acid / 100 mL aqueous solution), sonicate for 0.5 h, let stand for 48 h, and dry in a constant temperature oven at 60 °C for 12 h. Place the sample in a tube furnace and heat to 160 °C under a mixed atmosphere of nitrogen and hydrogen (hydrogen volume content 40%), and allow it to cool naturally after 1.5 h to obtain the sulfur-doped carbon nanocage platinum-supported catalyst. Figure 5 This is a TEM image of the prepared platinum-supported catalyst.
[0168] Preparation Example 2
[0169] This preparation example illustrates the preparation of nitrogen-containing carbon nanocages.
[0170] (1) Weigh 15g of basic nickel carbonate and 20.9g of ethylenediaminetetraacetic acid, add them to a beaker containing 40mL of deionized water, stir and mix them evenly at 80℃, and continue to heat and evaporate to dryness to obtain a solid precursor.
[0171] (2) Place the precursor obtained in step (1) into a ceramic boat, then place the ceramic boat in the constant temperature zone of a tube furnace, introduce nitrogen gas with a flow rate of 80 mL / min, and heat it to 600℃ at a rate of 10℃ / min. After holding the temperature for 1 hour, continue to heat it to 900℃ at a rate of 10℃ / min and hold the temperature for 2 hours. Stop heating and cool it to room temperature under a nitrogen atmosphere to obtain the pyrolysis product.
[0172] (3) Add the pyrolysis product obtained in step (2) to an aqueous solution containing 2M hydrochloric acid and stir at 90°C for 8 hours. Then filter, collect the filtrate, wash with deionized water until the filtrate is neutral, and then dry the filter cake in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-containing nano carbon cages.
[0173] TEM characterization of the carbon nanocages shows that the prepared material is a hollow cage-like carbon nanomaterial with a size of 5-20 nm.
[0174] The following examples illustrate sulfur-nitrogen co-doped carbon nanocages and platinum-supported catalysts and their preparation.
[0175] Example B-1
[0176] (1) Preparation of sulfur-nitrogen co-doped carbon nanocages
[0177] Take 0.12 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.02 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-nitrogen co-doped carbon nanocages. Figure 6 The sulfur-nitrogen co-doped nano-carbon cage TEM obtained. Figure 7 XPS S2p image of the prepared sulfur-nitrogen co-doped nanocages. Figure 8 XPS N1s images of the prepared sulfur-nitrogen co-doped carbon nanocages show that, according to X-ray photoelectron spectroscopy, the molar percentages of pyrrole nitrogen and pyridine nitrogen in the nitrogen on the surface of the sulfur-doped graphitized carbon nanocages are 100%. Based on the total molar amount of nitrogen, X-ray photoelectron spectroscopy shows that the molar percentages of pyrrole nitrogen and pyridine nitrogen in the nitrogen on the surface of the sulfur-doped graphitized carbon nanocages are 70.86% and 29.14%, respectively. The atomic percentage of each element can be calculated from the peak areas of the XPS spectra. Raman spectroscopy was used to determine the I... D / I G The value is 0.99. The BJH pore size distribution measured by BET shows that the material has two mesopore distribution peaks at 3.51 nm and 11.22 nm.
[0178] (2) Preparation of platinum-supported catalysts
[0179] 0.06 g of sulfur-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added with stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The resulting mixture was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst. Figure 9 This is a TEM image of the prepared platinum-supported catalyst.
[0180] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0181] Example B-2
[0182] (1) Preparation of sulfur-nitrogen co-doped carbon nanocages
[0183] 0.12 g of nitrogen-containing carbon nanocages prepared in Preparation Example 2 were added with 0.02 g of sulfur, ground for 5 minutes, and then calcined in an atmosphere furnace at 1100 °C for 2 hours. The heating rate was 5 °C / min, resulting in sulfur-nitrogen co-doped carbon nanocages. X-ray photoelectron spectroscopy (XPS) showed that the molar percentages of pyrrole nitrogen and pyridine nitrogen on the surface of the sulfur-doped graphitized carbon nanocages were 87.99%. Based on the total molar amount of nitrogen, XPS showed that the molar percentages of pyrrole nitrogen and pyridine nitrogen on the surface of the sulfur-doped graphitized carbon nanocages were 71.23% and 16.76%, respectively.
[0184] (2) Preparation of platinum-supported catalysts
[0185] 0.06 g of sulfur-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0186] The contents of each element in the sulfur-doped nano-carbon cage and the contents of platinum in the catalyst are listed in Table 1.
[0187] Example B-3
[0188] (1) Preparation of sulfur-nitrogen co-doped carbon nanocages
[0189] Take 0.12 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.02 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 700 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-nitrogen co-doped carbon nanocages.
[0190] (2) Preparation of platinum-supported catalysts
[0191] 0.06 g of sulfur-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0192] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0193] Example B-4
[0194] (1) Preparation of sulfur-nitrogen co-doped carbon nanocages
[0195] Take 0.12 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.04 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-nitrogen co-doped carbon nanocages.
[0196] (2) Preparation of platinum-supported catalysts
[0197] 0.06 g of sulfur-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0198] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0199] Example B-5
[0200] (1) Preparation of sulfur-nitrogen co-doped carbon nanocages
[0201] Take 0.10 g of nitrogen-containing carbon nanocage prepared in Preparation Example 2, add 0.01 g of sulfur, grind for 5 minutes, and calcine in an atmosphere furnace at 900 °C for 2 hours. The heating rate is 5 °C / min to obtain sulfur-nitrogen co-doped carbon nanocages.
[0202] (2) Preparation of platinum-supported catalysts
[0203] 0.06 g of sulfur-nitrogen co-doped carbon nanocage material was dispersed in 20 mL of deionized water, and a certain amount of chloroplatinic acid was added. The mixture was ultrasonically dispersed to form a suspension, and sodium carbonate aqueous solution was added to adjust the pH of the system to 10. The suspension was heated to 80 °C, and formic acid was added under stirring to carry out a reduction reaction. The molar ratio of reducing agent to platinum precursor was 5:1, and the reaction was maintained for 8 h. The mixture after the reaction was filtered, washed until the pH of the solution was neutral, and dried at 100 °C to obtain the platinum-supported catalyst.
[0204] The contents of each element in the sulfur-doped graphitized carbon nanocage and the contents of platinum in the catalyst are listed in Table 1.
[0205] Example B-6
[0206] Preparation of platinum-supported catalysts
[0207] Take 0.1 g of the sulfur-nitrogen co-doped carbon nanocage prepared in Example B-1, add 2.73 mL of chloroplatinic acid aqueous solution (1 g chloroplatinic acid / 100 mL aqueous solution), sonicate for 0.5 h, let stand for 48 h, and dry in a constant temperature oven at 60 °C for 12 h. Place the sample in a tube furnace and heat to 160 °C under a mixed atmosphere of nitrogen and hydrogen (hydrogen volume content 40%), and allow it to cool naturally after 1.5 h to obtain a sulfur-doped carbon nanocage platinum-supported catalyst. Figure 10 This is a TEM image of the prepared platinum-supported catalyst.
[0208] Example B-7
[0209] Preparation of platinum-supported catalysts
[0210] Take 0.1 g of the sulfur-nitrogen co-doped carbon nanocage prepared in Example B-1, add 1.37 mL of chloroplatinic acid aqueous solution (1 g chloroplatinic acid / 100 mL aqueous solution), sonicate for 0.5 h, let stand for 48 h, and dry in a constant temperature oven at 60 °C for 12 h. Place the sample in a tube furnace and heat to 160 °C under a mixed atmosphere of nitrogen and hydrogen (hydrogen volume content 40%), and allow it to cool naturally after 1.5 h to obtain a sulfur-doped carbon nanocage platinum-supported catalyst.
[0211] Table 1
[0212]
[0213]
[0214] The ORR performance of the platinum-supported catalysts prepared in the above examples and comparative examples is shown in Table 2 below.
[0215] Table 2
[0216]
[0217] The HER performance of the platinum-supported catalysts prepared in the above examples is shown in Table 3 below.
[0218] Table 3
[0219]
[0220]
[0221] Note: Comparative example (40% commercial PtC, JM 40% platinum-carbon catalyst, purchased from Beijing Innocare Technology Co., Ltd.)
[0222] The data above show that the sulfur-doped graphitized carbon nanocage combined with the noble metal platinum provided by this invention can improve the catalytic activity of the catalyst and has good application effects in ORR and HER. The platinum-carbon catalyst provided by this invention can achieve comparable or better results than commercial catalysts with high platinum loadings, even with relatively low platinum loadings.
[0223] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A carbon-based catalyst containing platinum for use in water electrolysis or proton exchange membrane hydrogen fuel cells, characterized in that, The catalyst comprises a support and platinum supported on the support, wherein the support is a sulfur-doped graphitized carbon nanocage with a hollow cage-like structure having a diameter of 2-100 nm and a sulfur atom molar percentage of 0.5-10% as measured by XPS. In the Raman curve of the sulfur-doped graphitized carbon nanocage, the value of ID / IG is less than 1.2; The sulfur-doped graphitized carbon nanocage has two or more mesopore distribution peaks; the first most probable pore size of the sulfur-doped graphitized carbon nanocage is 2-5 nanometers, and the second most probable pore size is 10-30 nanometers.
2. The carbon-based catalyst containing platinum according to claim 1, wherein, The sulfur-doped graphitized carbon nanocage has a hollow cage-like structure with a diameter of 2-50 nm. And / or, the molar percentage of carbon in the sulfur-doped graphitized carbon nanocage, as determined by X-ray photoelectron spectroscopy, is 60-98%, the molar percentage of sulfur is 0.5-10%, and the molar percentage of oxygen is 0.5-30%.
3. The carbon-based catalyst containing platinum according to claim 2, wherein, The sulfur-doped graphitized carbon nanocage has a hollow cage-like structure of 5-30 nm.
4. The carbon-based catalyst containing platinum according to claim 1, wherein, In the Raman curve of the sulfur-doped graphitized carbon nanocage, I D / I G The value is less than 1.
1.
5. The carbon-based catalyst containing platinum according to claim 1, wherein, The thickness of the sulfur-doped graphitized carbon nanocage is 1-10 layers of graphitized carbon atoms.
6. The carbon-based catalyst containing platinum according to claim 1, wherein, The sulfur-doped graphitized carbon nanocages also contain nitrogen, with a nitrogen atom molar percentage of 0.5-10% as measured by XPS.
7. The carbon-based catalyst containing platinum according to claim 6, wherein, X-ray photoelectron spectroscopy revealed that the sulfur-doped graphitized carbon nanocages contained 60-98% carbon, 0.5-10% nitrogen, 1-25% oxygen, and 0.5-5% sulfur.
8. The carbon-based catalyst containing platinum according to claim 7, wherein, X-ray photoelectron spectroscopy revealed that the sulfur-doped graphitized carbon nanocages contained 85-97% carbon, 0.5-3% nitrogen, 2-13% oxygen, and 0.5-4.5% sulfur.
9. The carbon-based catalyst containing platinum according to claim 6, wherein, X-ray photoelectron spectroscopy showed that the molar percentage of pyrrole nitrogen and / or pyridine nitrogen in the nitrogen on the surface of the sulfur-doped graphitized carbon nanocage was greater than 80%.
10. The carbon-based catalyst containing platinum according to claim 9, wherein, Based on the total molar amount of nitrogen, X-ray photoelectron spectroscopy determined that the molar percentage of pyrrole nitrogen in the nitrogen on the surface of the sulfur-doped graphitized carbon nanocage was 70-100%, and the molar percentage of pyridine nitrogen was 0-30%.
11. The carbon-based catalyst containing platinum according to claim 1, wherein, The method for preparing the sulfur-doped graphitized carbon nanocages includes the following steps: (1) Provide a solution containing a transition metal salt, a carbon source and a solvent, and then dry it to obtain a precursor; (2) Under an inert or reducing atmosphere, the precursor obtained in step (1) is subjected to high-temperature pyrolysis at a temperature of 850-1300℃ to obtain pyrolysis products. (3) The pyrolysis product is acid washed, and then solid-liquid separation and drying are performed to obtain nano-carbon cages; The method further includes steps (4-1) and / or (4-2), wherein, (4-1) The nano-carbon cage is mixed with a sulfur source and then subjected to high-temperature treatment at 300-1500℃; (4-2) The nano-carbon cage is impregnated with an impregnation solution containing a sulfur source and then dried.
12. The carbon-based catalyst containing platinum according to claim 11, wherein, In step (1), The carbon source is a nitrogen-free carbon source and / or a nitrogen-containing carbon source; And / or, the transition metal salt is selected from one or more of the organic acid salts, carbonates, and basic carbonates of transition metals; And / or, the transition metal is at least one of iron, cobalt, nickel and copper; And / or, the molar ratio of the transition metal salt to the carbon source, calculated as a transition metal element, is 1:0.1-10; And / or, the solvent is water.
13. The carbon-based catalyst containing platinum according to claim 12, wherein, In step (1), The nitrogen-free carbon source is at least one of citric acid, maleic acid, pyromellitic acid, terephthalic acid, and malic acid; the nitrogen-containing carbon source is ethylenediaminetetraacetic acid. And / or, the organic acid salt of the transition metal is an organic carboxylate salt of the transition metal that does not contain heteroatoms; And / or, the transition metal is nickel; And / or, the molar ratio of the transition metal salt to the carbon source, calculated as a transition metal element, is 1:0.5-5.
14. The carbon-based catalyst containing platinum according to claim 13, wherein, In step (1), The nitrogen-free carbon source is citric acid; And / or, the organic acid salt of the transition metal is an acetate; And / or, the molar ratio of the transition metal salt to the carbon source, calculated as a transition metal element, is 1:0.6-0.
9.
15. The carbon-based catalyst containing platinum according to claim 11, wherein, In step (2), The high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 1-20℃ / min, and then maintaining a constant temperature; And / or, the isothermal time is 20-600 min; And / or, the temperature of the high-temperature pyrolysis is 900-1200℃; And / or, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium; the reducing atmosphere is provided by hydrogen and optionally an inert gas.
16. The carbon-based catalyst containing platinum according to claim 15, wherein, In step (2), The high-temperature pyrolysis process includes: heating to the high-temperature pyrolysis temperature at a rate of 5-10℃ / min, and then maintaining a constant temperature; And / or, the isothermal time is 60-480 min.
17. The carbon-based catalyst containing platinum according to claim 11, wherein, In step (3), The pickling agent used to pickle the pyrolysis products is an aqueous solution of inorganic acid and / or an aqueous solution of organic acid; And / or, the pH value of the inorganic acid aqueous solution or the organic acid aqueous solution is less than 7; And / or, the pickling temperature is 20-120℃; the time is 0.1-48h.
18. The carbon-based catalyst containing platinum according to claim 17, wherein, In step (3), The pickling agent used to pickle the pyrolysis products is at least one of hydrochloric acid aqueous solution, sulfuric acid aqueous solution, nitric acid aqueous solution and citric acid aqueous solution; And / or, the pickling temperature is 60-100℃; the time is 4-12h.
19. The carbon-based catalyst containing platinum according to claim 18, wherein, In step (3), The acid washing agent used to acid wash the pyrolysis products is an aqueous solution of hydrochloric acid.
20. The carbon-based catalyst containing platinum according to claim 11, wherein, In step (4-1), The high-temperature treatment temperature is 400-1200℃; And / or, the high-temperature treatment time is 30-300 min; And / or, the sulfur source is selected from at least one of sulfur, hydrogen sulfide, carbon disulfide, sodium thiosulfate, thiophene, sulfate and sulfonate; And / or, the amount of the carbon nanocage and the sulfur source is such that the sulfur-doped graphitized carbon nanocage obtained has a sulfur atom molar percentage content of 0.5-10% as measured by XPS.
21. The carbon-based catalyst containing platinum according to claim 11, wherein, In step (4-2), The sulfur source is selected from at least one of sulfur, sodium thiosulfate, thiophene, sulfate and sulfonate; And / or, the solvent in the impregnation solution is selected from one or more of CCl4, CS2, cyclohexane and n-hexane; And / or, the concentration of the sulfur source in the impregnation solution is 0.0004-0.02 g / mL; And / or, the amount of the carbon nanocage and the sulfur source used is such that the molar percentage of sulfur atoms in the sulfur-doped graphitized carbon nanocage obtained is 0.5-10% as measured by XPS; And / or, relative to 1g of the nano-carbon cage, the amount of the impregnation solution used is 5-15mL; And / or, the drying conditions include: a temperature of 20-100°C and a time of 5-10 hours.
22. The carbon-based catalyst containing platinum according to claim 1, wherein, Based on the total amount of the carbon-based catalyst, the platinum mass percentage is 0.5-70%.
23. A method for preparing a platinum-containing carbon-based catalyst for water electrolysis or fuel cells according to any one of claims 1-22, the method comprising: After mixing the support with the platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction or gas-phase reduction. The carrier is a graphitized carbon nanocage doped with sulfur.
24. The preparation method according to claim 23, wherein, The amount of support and platinum source used is such that, based on the total amount of the carbon-based catalyst, the mass percentage of platinum in the prepared catalyst is 0.5-70%.
25. The preparation method according to claim 23, wherein, After mixing the support and platinum source in the presence of a solvent, a carbon-based catalyst containing metallic platinum is obtained by liquid-phase reduction, including: The support and platinum source were mixed in the presence of a solvent, the pH was adjusted, a reducing agent was added for reduction, and then dried to obtain a carbon-based catalyst containing metallic platinum.
26. The preparation method according to claim 25, wherein, Adjust the pH to 8-12.
27. The preparation method according to claim 25, wherein, The platinum source is selected from at least one of chloroplatinic acid, potassium chloroplatinate, and sodium chloroplatinate; and / or the concentration of the platinum source is 0.5-5 mol / L.
28. The preparation method according to claim 25, wherein, The reducing agent is selected from one or more of citric acid, ascorbic acid, formaldehyde, formic acid, ethylene glycol, sodium citrate, hydrazine hydrate, sodium borohydride, and glycerol.
29. The preparation method according to claim 25, wherein, The molar ratio of the reducing agent to the platinum source (calculated as Pt) is 2-100.
30. The preparation method according to claim 25, wherein, The reduction temperature is 50-150℃, and the reduction time is 2-15h.
31. The preparation method according to claim 23, wherein, After mixing the support and platinum source in the presence of a solvent, carbon-based catalysts containing metallic platinum are obtained by gas-phase reduction, including: The carrier and platinum source are mixed in the presence of a solvent, and the solvent is removed to obtain a precursor material. The precursor material is then heat-treated in a reducing atmosphere.
32. The preparation method according to claim 31, wherein, The precursor material is subjected to heat treatment at 80-300℃ for 1-4 hours.
33. The preparation method according to claim 31, wherein, The platinum source is selected from at least one of chloroplatinic acid, chloroplatinate, tetraammineplatinum acetate, and platinum acetylacetonate.
34. The preparation method according to claim 31, wherein, The solvent is one or more of water, alcohol solvents, and ketone solvents.
35. The preparation method according to claim 34, wherein, The solvent is water and / or ethanol.
36. The preparation method according to claim 31, wherein, Before removing the solvent, the mixed materials are allowed to stand for at least 10 hours.
37. The preparation method according to claim 35, wherein, Before removing the solvent, the mixed materials are allowed to stand for 15-24 hours.
38. The preparation method according to claim 31, wherein, The drying temperature during solvent removal is below 100℃.
39. The preparation method according to claim 31, wherein, The reducing atmosphere is provided by hydrogen and optionally an inert gas.
40. The preparation method according to claim 39, wherein, The reducing atmosphere is provided by a mixture of hydrogen and nitrogen.
41. The preparation method according to claim 40, wherein, The hydrogen content in the mixed atmosphere is 5-50% by volume.
Citation Information
Patent Citations
Preparation method of hollow carbon nanocage loaded platinum-based composite catalysts
CN102600835A
Carbon-based metal-free electrocatalyst for promoting polysulfide conversion in lithium-sulfur battery
CN108400285A
Methods for synthesizing carbon nanocages
US20180257940A1